Ruminal parameters of bovines fed diets based on sugar cane with doses of calcium hydroxide - Alexandre Menezes Dias; Luís Carlos Vinhas Ítavo; Julio Cesar Damasceno; Geraldo Tadeu dos Santos; Ériklis Nogueira; Camila Celeste Brandão Ferreira Ítavo (Revista Brasileira de Zootecnia, 2012)
The objective of this study was to evaluate the administration of different doses of calcium hydroxide mixed with sugar cane fed to cows by the pH, ammonia nitrogen and volatile fatty acids concentration in ruminal content. Four cows with fistulated rumen were distributed in a Latin square (4 × 4) in split plot. The treatments involved adding doses of 0, 8, 16 and 24 g/kg of calcium hydroxide to sugar cane in natura. Samples of rumen fluid were collected and the pH and concentration of N-NH3 was determined before (time zero) and 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 and 12 hours after the feeding time. The concentration of volatile fatty acids at 0, 3, 6, 9 and 12 hours was also determined. The calcium hydroxide contributed to maintain the pH of rumen fluid close to neutral. The average concentrations of N-NH3 in the ruminal fluid was 20.59, 20.49, 17.28 and 18.22 mg/100 mL for samples with calcium hydroxide at 0, 8, 16, 24 g/kg, respectively. There was an effect of the addition of calcium hydroxide on the volatile fatty acids concentration from before feeding until 12 hours after feeding time. There was an effect on doses tested for the concentration of volatile fatty acids. The calcium hydroxide added to the sugar cane influences on ruminal parameters. The dose of approximately 10 g of calcium hydroxide per kg sugar cane in natura is recommended.